2017
DOI: 10.3389/fmicb.2017.01254
|View full text |Cite
|
Sign up to set email alerts
|

Synechococcus Assemblages across the Salinity Gradient in a Salt Wedge Estuary

Abstract: Synechococcus are the most abundant and widely distributed picocyanobacteria in the ocean. The salt-wedge type of estuary possesses the complete horizontal and vertical gradient of salinity together with other physical and chemical parameters. In order to reveal whether such a complex environmental gradient harbors a high diversity of Synechococcus, we investigated the abundance, taxonomic composition and pigment genetic diversity of Synechococcus in surface and bottom waters across the salinity gradient in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 59 publications
12
58
0
Order By: Relevance
“…PT 3 was found to be largely dominant over PT 1 and 2 along the oceanic Tara Oceans transect, in agreement with the coastalrestricted distribution of the latter PTs (18,22,27,(31)(32)(33)(34)(37)(38)(39). Biogeography and correlation analyses with environmental pa-rameters provided several important insights concerning niche partitioning of PT 3 subtypes.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…PT 3 was found to be largely dominant over PT 1 and 2 along the oceanic Tara Oceans transect, in agreement with the coastalrestricted distribution of the latter PTs (18,22,27,(31)(32)(33)(34)(37)(38)(39). Biogeography and correlation analyses with environmental pa-rameters provided several important insights concerning niche partitioning of PT 3 subtypes.…”
Section: Discussionsupporting
confidence: 70%
“…Marine Synechococcus display a large pigment diversity, with different PTs preferentially harvesting distinct regions of the light spectrum. Previous studies based on optical properties or on a single genetic marker could not differentiate all PTs (17,(29)(30)(31), and thus neither assess their respective realized environmental niches (43) nor the role of light quality on the relative abundance of each PT. Here, we showed that a metagenomic read recruitment approach combining three genetic markers can be used to reliably predict all major PTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another ubiquitous marine cyanobacterium, Synechococcus, has been shown to have high genetic diversity associated with pigment diversity. Multiple gene variants, gene organisations, and even polymorphic intergenic spacer regions have been shown to be associated with unique geographic, thermal, and turbidity niches (Xia et al 2015(Xia et al , 2017. Possession of these unique genomic sequences and motifs appears to result in niche differentiation that expands the geographic range of the genus beyond where individual phylotypes could persist.…”
Section: Connecting Ancient and Recent Evolutionary History With Contmentioning
confidence: 99%
“…Possession of these unique genomic sequences and motifs appears to result in niche differentiation that expands the geographic range of the genus beyond where individual phylotypes could persist. Further whole-genome analysis could provide new insights into the genomic basis of these pigment-related traits, constraints on their variation owing to linkage or epistasis, and their associations with other traits under selection (Xia et al 2017). The existing genomic studies of natural populations of keystone primary producers reveal our staggering ignorance about the functional importance of genomic diversity in our global ecosystems.…”
Section: Connecting Ancient and Recent Evolutionary History With Contmentioning
confidence: 99%